Pediatric Critical Care Review - Hasan, Rashed A.; Hasan, Rashed A. (Humana Press : Imprint: Humana, 2006)
Pediatric critical care is an advancing science that requires both constant renewal of previously learned knowledge and exposure to new material. In Pediatric Critical Care Review, Board-certified pediatric critical care physicians uniquely capture the essence of the most common critical care scenarios in a series of carefully crafted questions, answers, rationales, and references. With their crisp and clear explanations, detailed references, and pertinent pictures, the authors illuminate-in an easy-to-read format-the essential facts and latest findings concerning the diagnosis and treatment of critical problems in the respiratory, cardiovascular, central nervous, endocrine, and gastrointestinal systems. Drawing on years of practical experience, they illuminate with simple, straightforward explanations the major clinical issues involved in the critical care of pediatric infectious diseases, hematology, oncology, immunology, metabolic disorders, pain management, and traumatology. Highly instructive and engagingly simple to use, Pediatric Critical Care Review offers busy clinicians, residents, fellows, and medical students rapid refreshment of what they have already learned and what they need to know about new approaches to the diagnosis and treatment of the most common childhood intensive care problems.